Criminal intimacy: prison and the uneven history of modern American sexuality - Kunzel, Regina G. (University of Chicago Press, 2008)
"An architecture adapted to morals" -- "Every prison has its perverts" -- The problem of prison sex in the mid-twentieth century -- "The deviants are the heterosexuals" : the quandaries of prison lesbianism -- The jungle : rape, race, and the violent prison -- "Lessons in being gay" -- Epilogue: the burdens of history